1D and 2D model coupling approach for the development of operational spatial flood early warning system. Issue 15 (22nd August 2022) - Kalimisetty, Sindhu; Singh, Amanpreet; Korada Hari Venkata, Durga Rao; V, Venkateshwar Rao; Mahammood, Vazeer
Abstract: Main aim of the paper is to emphasise the advantage of 1 D and 2 D hydrodynamic models coupling in simulating flood inundations using high resolution Digital Terrain Models. The developed flood early warning model was calibrated and validated thoroughly at critical locations using historic observed discharge data and point rainfall data of about 350 stations. The flood inundation simulation model was prepared using flexible mesh approach and compared with the satellite imagery of Radarsat2. 1 D hydrodynamic model was integrated with 2 D hydrodynamic model by standard links for seamless hydrodynamic modelling. It is found that computational time has reduced drastically due to integration of 1 D and 2 D hydrodynamic models. Web-enabled spatial flood early warning system is developed to disseminate flood advisories in real-time. Computed peak discharge is found to be more than 87% accurate with forecast lead time of 52 hours when compared with field measurements subsequently.